Constraints in Adoption of Scientific Fish Farming in Nagaon District, Assam - Manas Pratim Dutta,; Binod Kalita,, Shah Mustahid Hussain, Kaustabh Bhagawati, (Indian Journal of Extension Education, 2022)
The study is conducted at two randomly selected development blocks of Nagaon district, Assam viz. Rupahi and Kaliabor Block during 2019-2021 to find out the constraints faced by the farmers in the adoption of scientific fish farming. A total of 50 farmers from each of the selected blocks were finally selected through simple random sampling. A structured questionnaire consisting of 20 questions was used to collect responses about scientific fish farming problems and related information specifically based on the preliminary survey as well as focus group discussions and Constraint Index (CI) was calculated. Lack of quality fish seed of required size and number at the time of stock (CI 1.66) in both Kaliabor and Rupahi blocks were the most common constraint and poaching of fish (CI 0.05) was the least common constraint. It was also observed that most of the adopters in the studied area were within the age group of 18 to 30 years which calls for better entrepreneurship and employment generation.